Detection of RNA-binding Proteins by RNA Pull-down in Adipocyte Culture - Bai, Qianfan (2017)
RNA-binding proteins (RBPs) are emerging as a regulatory layer in the development and function of adipose. RBPs play a key role in the gene expression regulation at posttranscriptional levels by affecting the stability and translational efficiency of target mRNAs. RNA pull-down technique has been widely used to study RNA-protein interaction, which is necessary to elucidate the mechanism underlying RBPs' as well as long non-coding RNAs' (lncRNAs) function. However, the high lipid abundance in adipocytes poses a technical challenge in conducting this experiment. Here a detailed RNA pull-down protocol is optimized for primary adipocyte culture. An RNA fragment from androgen receptor's (AR) 3' untranslated region (3'UTR) containing an adenylate-uridylate-rich elementwas used as an example to demonstrate how to retrieve its RBP partner, HuR protein, from adipocyte lystate. The method described here can be applied to detect the interactions between RBPs and noncoding RNAs, as well as between RBPs and coding RNAs.